Long-Term Results of the TARGIT-A Trial: More Questions than Answers - Piroth, Marc D.; Strnad, Vratislav; Krug, David; Fastner, Gerd; Baumann, Rene; Combs, Stephanie E.; Duma, Marciana Nona; Dunst, Juergen; Feyer, Petra; Fietkau, Rainer; Haase, Wulf; Harms, Wolfgang; et al. (Breast Care, 2021)
Background: During the last decade, partial breast irradiation (PBI) has gained traction as a relevant treatment option for patients with early-stage low-risk breast cancer after breast-conserving surgery. The TARGIT-A prospective randomized trial compared a "risk-adapted" intraoperative radiotherapy (IORT) approach with 50-kv X-rays (INTRABEAM (R)) as the PBI followed by optional whole-breast irradiation (WBI) and conventional adjuvant WBI in terms of observed 5-year in-breast recurrence rates. Recently, long-term data were published. Since the first publication of the TARGIT-A trial, a broad debate has been emerged regarding several uncertainties and limitations associated with data analysis and interpretation. Our main objective was to summarize the data, with an emphasis on the updated report and the resulting implications. Summary: From our point of view, the previously unresolved questions still remain and more have been added, especially with regard to the study design, a change in the primary outcome measure, the significant number of patients lost to follow-up, and the lack of a subgroup analysis according to risk factors and treatment specifications. Key Message: Taking into account the abovementioned limitations of the recently published long-term results of the TARGIT-A trial, the German Society of Radiation Oncology (DEGRO) Breast Cancer Expert Panel adheres to its recently published recommendations on PBI: "the 50-kV system (INTRABEAM) cannot be recommended for routine adjuvant PBI treatment after breast-conserving surgery."
CRIS-Team WoS Importer:2021-04-23